2020
DOI: 10.3390/ijerph17124381
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Strength Training on Vastus Lateralis’ Stiffness: An Ultrasound Quasi-Static Elastography Study

Abstract: Ultrasound imaging allows the evaluation of musculoskeletal morphology and function. Ultrasound elastography can also offer semi-quantitative and/or quantitative assessment of tissue stiffness providing relevant information about adaptations of skeletal muscle mechanical properties. In this study we aimed to explore the feasibility of elastography ultrasound imaging in assessing the effect of strength training on vastus lateralis stiffness. Twenty-eight young male adults were separated in a control (n = 9) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
1
Order By: Relevance
“…A different exercise regime was administered by Santos et al in order to assess maximal concentric or eccentric training effects on vastus lateralis muscle characteristics [ 34 ]. Sedentary participants who were recruited for 15 weeks had to perform, at different range of motion (ROM) [ 35 ] angles, a leg extension exercise.…”
Section: Resultsmentioning
confidence: 99%
“…A different exercise regime was administered by Santos et al in order to assess maximal concentric or eccentric training effects on vastus lateralis muscle characteristics [ 34 ]. Sedentary participants who were recruited for 15 weeks had to perform, at different range of motion (ROM) [ 35 ] angles, a leg extension exercise.…”
Section: Resultsmentioning
confidence: 99%
“…Damaged muscle during and immediately after exercise becomes stiff over time with further exercise. 25 , 26 Early and rapid cryotherapy after exercises is helpful in controlling acute inflammation; as a result, the inflamed area and deterioration of muscle stiffness are suppressed. 13 , 27 Cryotherapy tends to slow the oxygen demand of mitochondria, thereby decreasing the metabolic demand and inflammation of the muscle.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this approach has been increasingly used to evaluate the muscle hardness of skeletal muscle [ 11 , 12 , 13 ]. Although some studies have reported increased muscle hardness after strength training using RTE [ 6 , 7 , 14 ], to the best of our knowledge, few studies have examined changes in lower extremity muscle hardness after aerobic exercise. Among aerobic exercises, water exercise has been reported to improve aerobic capacity [ 15 ], the range of joint motion [ 16 ], pain [ 17 ], and FFD [ 18 ] because of the physical properties of water (density, buoyancy, viscosity, and the effects of hydrostatic pressure and water temperature [ 19 , 20 ] compared with land-walking.…”
Section: Introductionmentioning
confidence: 99%